Empirical Impression - An Efficient Alternative for Ocular Rehabilitation: A Case Report - Patel, C. P.; Suwal, P.; Parajuli, P. K.; Sharma, A.; Basnet, B. B. (Journal of Nepalese Prosthodontic Society, 2021)
Ocular prostheses have been used since a very long time ago. Success of ocular prosthesis depends upon its adaptation with anopthalmic socket which is best determined by ocular impressions. Various impression techniques and materials have been described in the literature. This case report highlights the use of empirical impression technique for fabrication of ocular prosthesis of a 65-year old male who had undergone enucleation surgery of left eye. The empirical impression technique involves: first a close visual examination of patient’s socket, then a wax shell is designed and modified empirically to a shape that fits the socket; second, an impression is made of the socket, using this wax shell as an impression tray. Reduced treatment time and increased simplicity are the primary advantages of this method. This technique of impression making is not feasible in cases with highly irregular sockets.